Can small-side games provide adequate high-speed training in professional soccer? - Asian-Clemente, J.; Rabano-Muñoz, A.; Muñoz, B.; Franco, J.; Suarez-Arrones, L. (International Journal of Sports Medicine, 2021)
The aim was to compare the running activity in official matches with that achieved in two small-sided games, designed with the same relative area per player but with different constraints and field dimensions, aiming to stimulate high-speed and very-high-speed running. Seventeen young professional players played one 5 vs. 5+5 with 2 floaters, varying in terms of whether there was a change of playing area (SSGCA) or not change (SSGNC). Running activity was monitored using GPS and the following variables were recorded: total distance covered; high-speed distance (18-21 km·h-1); very high-speed distance (>21 km·h-1); peak speed; accelerations and decelerations between 2-3 m·s-2 and above 3 m·s-2. SSGCA achieved statistically higher total distance, high-speed, peak speed and number of accelerations and decelerations than SSGNC (large to small magnitude). Both drills showed statistically greater high speed, number of accelerations and decelerations than official matches (large to small magnitude). Moreover, SSGCA exhibited statistically more total distance and distance at higher speed than official matches (moderate and small magnitude, respectively). In contrast, official matches showed statistically higher peak speeds than both training tasks and more very high speed than SSGNC (large and moderate magnitude, respectively). Coaches could use SSGCA to promote greater running activity in soccer players.